2015
DOI: 10.1111/ene.12745
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between alexithymia, empathy and moral judgment in patients with multiple sclerosis

Abstract: Understanding such complex interactions between individual dispositions and moral cognition has the potential to contribute to the development of better assessment and intervention strategies for MS patients, enhancing quality of life by achieving better social participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 62 publications
9
56
0
4
Order By: Relevance
“…No specific areas of the brain were affected by demyelination or atrophy among patients with lower levels of empathy. These findings have added more data to the literature, and are in agreement with previous reports 10,11 . However, it must be highlighted that this study is not free of potential bias: patients and controls may have had difficulty in expressing their feelings in the short sentences used by this instrument.…”
Section: Discussionsupporting
confidence: 92%
“…No specific areas of the brain were affected by demyelination or atrophy among patients with lower levels of empathy. These findings have added more data to the literature, and are in agreement with previous reports 10,11 . However, it must be highlighted that this study is not free of potential bias: patients and controls may have had difficulty in expressing their feelings in the short sentences used by this instrument.…”
Section: Discussionsupporting
confidence: 92%
“…Subtle difficulties in recognizing others' emotional expressions, empathic abilities, reading their complex mental states and understanding pragmatic language statements (such as irony) can contribute to interpersonal problems observed in MS. Evidence also suggests that MS patients might also subjectively report difficulties in recognizing their own emotions and empathy (Chahraoui et al 2014;Gleichgerrcht et al 2015). White and gray matter pathology in MS affects multiple brain regions and disrupts a number of neural networks that play key roles in social cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with RRMS demonstrated significantly lower levels of empathy toward others and fantasy compared to healthy subjects [82]. An earlier study by Beatty conducted in 1989 with MS patients assessed their ability to identify facial affect by viewing photographs depicting basic emotional states.…”
Section: Relapsing-remitting Multiple Sclerosis (Rrms)mentioning
confidence: 99%
“…Paradoxically, regarding the emotion "fear" they showed better results than controls [6]. Gleichgerrcht et al found that MS subjects (patients n = 38; controls n = 38) had significantly higher self-oriented personal distress (p < 0.01) and higher levels of alexithymia compared to controls [82].…”
Section: Relapsing-remitting Multiple Sclerosis (Rrms)mentioning
confidence: 99%